2007
DOI: 10.1262/jrd.19021
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Ultrasonography of Xenografted Domestic Cat Ovarian Cortex

Abstract: Abstract. Transplantation of ovarian tissue has high potential for female gamete conservation. However, optimal timing of oocyte recovery for in vitro maturation and fertilization is still critical. Therefor the aim of the present study was to use high-resolution transcutaneous ultrasonography to monitor follicular development within xenografted ovarian tissue. Ovarian cortex fragments (n=44) from domestic cats were transplanted into athymic nude rats (n=12). Graft development in the animals was assessed weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…A potentially better approach will be to use all COCs to establish the necessary methods for oocytes cryopreservation and embryo production, as a prerequisite for handling oocytes obtained from ovarian tissue after xenotransplantation (Fassbender et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…A potentially better approach will be to use all COCs to establish the necessary methods for oocytes cryopreservation and embryo production, as a prerequisite for handling oocytes obtained from ovarian tissue after xenotransplantation (Fassbender et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Our group used BrdU-labeling and Hoechst staining for integrity assessment of mechanical isolated preantral follicles to control culture impacts [21], but it was shown that the procedure of isolation from the ovarian cortex itself can cause a loss of integrity in primordial follicles [22]. We also suggested the application of high-resolution ultrasound to monitor the survival of fresh ovarian xenotransplants in immunodeficient recipients as a prerequisite for oocytes retrieval [15]. The freezing of isolated preantral follicles as well as COCs is not well established yet for felid species.…”
Section: Discussionmentioning
confidence: 99%
“…Bosch et al [14] demonstrated the successful cryopreservation of domestic cat ovarian cortex in conjunction with xenotransplantation into nude mice. However, feline oocytes seem to express a higher sensitivity towards cryopreservation protocols [15,16] than other mammalian oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Yasmin et al (2015) confirmed that the meiotic spindles in bovine oocytes are very sensitive to low temperatures that can affect the level of maturation and fertilization. Feline oocytes seem to express a higher sensitivity to chilling (Fassbender et al, 2007).…”
Section: Fertilization Ratementioning
confidence: 97%
“…A cryopreservation protocol has been developed for preserving cat ovarian tissues with minimum effect on the survival of the follicles (Giaretta et al, 2013). However, feline oocytes seem to express a higher sensitivity towards cryopreservation protocols (Fassbender et al, 2007). Shorter preservation procedures using physiological solutions such as PBS stored at 4-5°C can provide an alternative way to save the source of germ cells such as ovary and testes.…”
Section: Introductionmentioning
confidence: 99%